Water non-dispersible cement paste system for well cementation

By adopting a specific water-free cement slurry system in the cementing of oil wells, the dissolution and migration of formation water to cement slurry and quality exchange problems are solved, and the good dispersion resistance and flow performance of cement slurry are achieved, ensuring the normal production of oil and gas wells.

CN119638277APending Publication Date: 2025-03-18CNPC BOHAI DRILLING ENG +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202311192478.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

During the cementing process of oil wells, the dissolution and migration of cement slurry by formation water and mass exchange have not been effectively solved, resulting in the impact of the cement ring structure and cementing quality, which seriously affects the normal production and operation of oil and gas wells.

Method used

A cementing water-free cementing slurry system is adopted, which includes oil well cement, expansion agent, anti-dispersant, drag reducing agent, defoaming agent and water. Through specific compositional proportions and preparation methods, cement slurry with good dispersion resistance and flow properties are formed.

Benefits of technology

The cement slurry system improves fluidity while maintaining good dispersion resistance, effectively improves the water-invasion resistance of cement slurry, solves the problems of dissolution and migration of formation water to cement slurry and quality exchange, and ensures the normal production and operation of oil and gas wells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a water-non-dispersible cement paste system for well cementation. The water-non-dispersible cement paste system comprises the following components in parts by weight: 100 parts of oil well cement, 2-3 parts of an expanding agent, 1-5 parts of an anti-dispersing agent, 0.5-2 parts of a drag reducer, 0-0.1 part of a defoaming agent and 40-45 parts of water, the anti-dispersing agent is formed by copolymerizing the following components in percentage by mass: 15 to 60 weight percent of acrylic acid, 0 to 15 weight percent of N, N-dimethyl acrylamide, 30 to 85 weight percent of acrylamide, 0 to 10 weight percent of N-vinyl pyrrolidone and 0 to 1.5 weight percent of ethylene diamine tetraacetic acid disodium salt; the drag reducer is obtained by graft polymerization of a polyacrylic acid monomer and fatty acid vinyl ester in a molar ratio of (8-36): 1; the polyacrylic acid monomer is formed by copolymerizing 2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium p-styrenesulfonate and acrylamide according to a molar ratio of (0.08 to 0.6): 1: (0.05 to 0.3): (0.1 to 1); the water non-dispersible cement paste system for well cementation has good dispersion resistance and flowing property, and the water invasion resistance of the cement paste is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oilfield cementing engineering, in particular to a cementing water non-dispersible cement slurry system. Background Art

[0002] At present, more than 70% of my country's crude oil production still relies on tapping the potential of old oil fields. However, the long-term water injection development of old oil fields has caused formation pressure disorder, increased water content in the formation, and an increase in high-pressure aquifers, which has led to widespread water invasion during the cementing process of adjustment wells in the water injection block. The hazards caused by formation water invasion are mainly reflected in three aspects: the invasion of formation water will dilute and reduce the density of cement slurry or dissolve and migrate cement slurry, thereby causing a decrease in static liquid column pressure and leading to pressure instability; after the formation water enters the cement slurry, it will directly affect the solidification process of cement slurry, thereby affecting the performance of the cement hardening body, destroying the structure and bonding quality of the cement sheath, and causing more serious harm than gas invasion; the invasion of formation fluids destroys the bonding quality of the two interfaces, forming a crossflow channel between the cement sheath and the formation, seriously affecting the normal production and operation of the later exploitation of oil and gas wells.

[0003] The three main factors that cause water invasion and water channeling are the high volume shrinkage and high water loss of oil well cement during construction, as well as the dissolution, migration and scouring of formation water on cement slurry, which destroys the solid phase structure of cement slurry. There have been many related research reports in China on the problems of high volume shrinkage and high filtration loss of cement slurry. At present, the main solution is to use expansion agents, filtration loss reducers and early strength agents to make cement slurry have the characteristics of low filtration loss, high early strength, double expansion (plastic expansion and hardening expansion), zero water release, short transition time, etc., thereby improving the problem of water channeling to a certain extent. However, the problems of "dissolution migration" and "mass exchange" of formation water on cement slurry have not been effectively solved, and there are few related studies.

[0004] At present, underwater non-dispersible concrete in the construction industry has provided a new idea for solving the problems of "dissolution migration" and "mass exchange" of formation water on cement slurry, that is, underwater non-dispersible concrete has excellent anti-dispersion, fluidity, water retention, coagulation and other properties, which are also important for oil well cement; however, since the applicable environments of the two are very different, the complex bottom well formation environment requires that oil well cement also has good fluidity, filtration loss and good mechanical properties after consolidation under high temperature and high pressure conditions. The flocculant used in concrete has the disadvantages of being not resistant to high temperature and easy to slow setting, and cannot be directly used in oil well cement. At the same time, the compatibility of concrete flocculants with admixtures such as drag reducers, retarders, and expansion agents for oil well cement also determines that traditional flocculants cannot be directly applied to oil well cement. Therefore, it is particularly important to invent an anti-dispersant suitable for oil well cement to form a set of cementing water non-dispersible cement slurry system that meets the requirements of downhole construction. Summary of the invention

[0005] The object of the present invention is to provide a non-dispersible cement slurry system for cementing water which improves the fluidity of cement slurry without affecting its anti-dispersion performance.

[0006] To this end, the technical solution of the present invention is as follows:

[0007] A non-dispersible cement slurry system for cementing water comprises, by weight, 100 parts of oil well cement, 2 to 3 parts of expansion agent, 1 to 5 parts of anti-dispersant, 0.5 to 2 parts of drag reducer, 0 to 0.1 parts of defoamer and 40 to 45 parts of water; wherein,

[0008] The anti-dispersion agent is a polyacrylamide flocculant copolymerized by mass fractions of 15wt.% to 60wt.% acrylic acid, 0wt.% to 15wt.% N,N-dimethylacrylamide, 30wt.% to 85wt.% acrylamide, 0wt.% to 10wt.% N-vinylpyrrolidone, and 0wt.% to 1.5wt.% disodium ethylenediaminetetraacetate;

[0009] The drag reducer is obtained by graft polymerization of fatty acid vinyl ester and polyacrylic acid monomer; the polyacrylic acid monomer is copolymerized by 2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium p-styrenesulfonate and acrylamide in a molar ratio of (0.08-0.6):1:(0.05-0.3):(0.1-1.0); the molar ratio of acrylic acid in the preparation of fatty acid vinyl ester and polyacrylic acid monomer is (8-36):1; the fatty acid vinyl ester is at least one of vinyl acetate, vinyl propionate and vinyl butyrate.

[0010] Preferably, the oil well cement is API oil well G grade cement.

[0011] Preferably, the specific preparation method of the anti-dispersant is:

[0012] Step 1, preparing 5wt.% to 30wt.% acrylic acid aqueous solution, and adding a pH adjuster dropwise to make the pH of the reaction system 4 to 9;

[0013] Step 2, adding N,N-dimethylacrylamide, acrylamide, N-vinyl pyrrolidone and disodium ethylenediaminetetraacetate to the reaction system, and stirring until dissolved;

[0014] Step 3, introducing an inert gas into the reaction system for at least 20 minutes, and then placing the reaction system in a constant temperature water bath at 30°C to 40°C, sequentially adding initiator A and initiator B into the reaction system, and stirring until dissolved;

[0015] Step 4: Place the reaction system under sealed conditions and continue the reaction at 30° C. to 40° C. for 2 h to 4 h to obtain a translucent gel-like anti-dispersion flocculant.

[0016] Preferably, in step 2 of preparing the anti-dispersant, after each addition of a monomer is completed, it is stirred until dissolved before adding the next monomer.

[0017] Preferably, in step 3 of preparing the anti-dispersant, initiator A is azomethylpropylimidazole hydrochloride, and its addition amount is 0.1wt.% to 1wt.% of the total weight of the comonomers; initiator B is a mixture of potassium persulfate and sodium bisulfite, and its addition amount is 0.1wt.% to 1wt.% of the total weight of the comonomers.

[0018] Preferably, the specific preparation method of the drag reducer is:

[0019] Step 1, dissolving 2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium p-styrenesulfonate and acrylamide in water to prepare a 40wt.% to 60wt.% reaction solution, and dropping a pH adjuster to adjust the pH of the reaction system to 2.5 to 6.5, then stirring and heating to 40°C to 80°C, adding initiator A and a chain transfer agent to the reaction system, and continuing the isothermal reaction under the above temperature conditions for 3h to 6h to obtain a polyacrylic acid macromonomer;

[0020] Step 2: Add fatty acid vinyl ester, molecular weight regulator and water to the polyacrylic acid macromonomer in sequence, stir and dissolve, heat the reaction system to 50°C to 90°C, and drop 20wt.% to 40wt.% of an aqueous solution of initiator B, and then continue to stir and react at a constant temperature for 1h to 3h; after the reaction is completed, drop a pH regulator to adjust the pH of the system to 5 to 7, and after cooling, obtain a graft copolymer drag reducer with a concentration of 20% to 40%.

[0021] Preferably, in the preparation step 1 of the drag reducer, the initiator A is ammonium persulfate, potassium persulfate or sodium persulfate, and its amount is 0.8wt.% to 5.0wt.% of the total weight of 2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium p-styrenesulfonate and acrylamide; the chain transfer agent is mercaptopropionic acid, thioglycolic acid or sodium methacrylic acid, and its addition amount is 0.01 times to 0.05 times the molar amount of acrylic acid.

[0022] Preferably, in the preparation step 2 of the drag reducer, the molecular weight regulator is n-dodecyl mercaptan or isopropanol, and the amount thereof added is 0.0005 to 0.001 times the molar amount of the fatty acid vinyl ester; the initiator B is dibenzoyl peroxide, lauroyl peroxide, diisopropyl peroxydicarbonate or dicyclohexyl peroxydicarbonate, and the amount thereof added is 0.8% to 1.5% of the total weight of 2-acrylamido-2-methylpropane sulfonic acid, acrylic acid, sodium p-styrene sulfonate, acrylamide and fatty acid vinyl ester.

[0023] Preferably, in the step 2 of preparing the drag reducing agent, the dripping time of the initiator B is controlled within 2 h to 5 h.

[0024] Preferably, the pH adjuster is a 0.4 wt. % sodium hydroxide aqueous solution or a 0.4 wt. % potassium hydroxide aqueous solution.

[0025] Preferably, the defoamer is a silicone ether copolymer defoamer, a polyether defoamer or a lipid defoamer.

[0026] Preferably, the water is tap water, deionized water or distilled water.

[0027] Compared with the existing technology, the non-dispersible cement slurry system for cementing water does not affect the anti-dispersion performance while improving the fluidity of the cement slurry, that is, it has both good anti-dispersion and fluidity, effectively improves the water invasion resistance of the cement slurry, and provides a new technical solution to the problems of "dissolution migration" and "mass exchange" of formation water on cement slurry. DETAILED DESCRIPTION

[0028] The present invention will be further described below in conjunction with specific examples, but the following examples are by no means intended to limit the present invention in any way.

[0029] Example 1

[0030] A non-dispersible cement slurry system for cementing water comprises, by weight, 100 parts of G-grade oil well cement, 2 parts of expansion agent, 1 part of anti-dispersant, 0.5 parts of drag reducer, 0.1 parts of defoamer and 44 parts of water, and is prepared according to the method specified in the standard GB / T 19139 oil well cement test method.

[0031] In this embodiment 1, the G-grade oil well cement is the G-grade cement produced by Shandong Shengwei Special Cement Co., Ltd.; the expansion agent is the BH-P801S expansion agent produced by PetroChina Bohai Drilling Engineering Co., Ltd.; the defoamer is the BZXP-1 tributyl phosphate defoamer produced by PetroChina Bohai Drilling Engineering Co., Ltd.; the anti-dispersant and the drag reducer are prepared by the laboratory; specifically,

[0032] The preparation method of the anti-dispersion agent is as follows: 1) dissolving 10g of acrylic acid in water to obtain a 10wt.% aqueous solution, and adding 0.4wt.% sodium hydroxide aqueous solution to adjust the pH of the reaction system to 6.5; 2) adding 1g of N,N-dimethylacrylamide, 8g of acrylamide, 1g of N-vinylpyrrolidone and 0.2g of disodium ethylenediaminetetraacetate to the reaction system, and stirring until dissolved; 3) introducing an inert gas into the reaction system for at least 20min, and then placing it at 35°C, first adding 0.2g of azomethylpropylimidamide hydrochloride to the reaction system, and then adding 0.2g of a mixture of potassium persulfate and sodium bisulfite (the molar ratio of the two is 1:1); 4) placing the reaction system under sealed conditions, and continuing the reaction at 35°C for 4h to obtain a translucent gel-like anti-dispersion flocculant.

[0033] The specific preparation method of the drag reducer is as follows: 1) 16.56g of 2-acrylamido-2-methylpropanesulfonic acid, 72g of acrylic acid, 10.3g of sodium p-styrenesulfonate, 7.1g of acrylamide and 70.6g of water are stirred and dissolved uniformly to prepare a mixed aqueous solution with a mass concentration of 50%, and 0.4wt.% of sodium hydroxide aqueous solution is added dropwise to adjust the pH of the reaction system to 2.5, and after stirring and heating to 40°C, 0.8477g of ammonium persulfate and 5.3g of mercaptopropionic acid are added, and the reaction is continued at 40°C for 5h to obtain a polyacrylic acid macromonomer; 2) Add 688g of vinyl acetate, 0.808g of n-dodecyl mercaptan and 1191g of water to the polyacrylic acid macromonomer, stir for 10min between each addition, then heat to 50°C, and then drop 32g of a 20wt.% aqueous solution of dibenzoyl peroxide thereto for 2h. After the dropwise addition is completed, continue to stir and react at a constant temperature for 2h. After the reaction is completed, adjust the pH of the system to 5 with a 0.4wt.% aqueous solution of sodium hydroxide, cool naturally, and obtain a drag reducer with a concentration of 40%.

[0034] Example 2

[0035] A non-dispersible cement slurry system for cementing water comprises, by weight, 100 parts of G-grade oil well cement, 2 parts of swelling agent, 2 parts of anti-dispersant, 0.5 parts of drag reducer, 0.1 parts of defoamer and 43 parts of water, and is prepared according to the method specified in the standard GB / T 19139 oil well cement test method; in this embodiment 2, the specific selection of G-grade oil well cement, swelling agent, defoamer, anti-dispersant and defoamer is consistent with that in embodiment 1.

[0036] Example 3

[0037] A non-dispersible cement slurry system for cementing water comprises, by weight, 100 parts of G-grade oil well cement, 2 parts of expansion agent, 3 parts of anti-dispersion agent, 0.5 parts of drag reducer, 0.1 parts of defoamer and 42 parts of water, and is prepared according to the method specified in the standard GB / T 19139 oil well cement test method; in this embodiment 3, the G-grade oil well cement adopts the G-grade cement produced by Shandong Shengwei Special Cement Co., Ltd.; the expansion agent adopts the BH-P801S expansion agent produced by PetroChina Bohai Drilling Engineering Co., Ltd.; the defoamer adopts the BZXP-1 tributyl phosphate defoamer produced by PetroChina Bohai Drilling Engineering Co., Ltd.; the anti-dispersion agent and the drag reducer are prepared in the laboratory; wherein,

[0038] The preparation method of the anti-dispersion agent is as follows: 1) dissolving 12g of acrylic acid in water to obtain a 12wt.% aqueous solution, and adding dropwise 0.4wt.% sodium hydroxide aqueous solution to adjust the pH of the reaction system to 6.5; 2) adding 1g of N,N-dimethylacrylamide, 6.5 of acrylamide, 1g of N-vinylpyrrolidone and 0.2g of disodium ethylenediaminetetraacetate to the reaction system, and stirring until dissolved; 3) introducing an inert gas into the reaction system for at least 20min, and then placing it at 35°C, first adding 0.2g of azomethylpropylimidamide hydrochloride to the reaction system, and then adding 0.2g of a mixture of potassium persulfate and sodium bisulfite (the molar ratio of the two is 1:1); 4) placing the reaction system under sealed conditions, and continuing the reaction at 35°C for 4h to obtain a translucent gel-like anti-dispersion flocculant.

[0039] The specific preparation method of the drag reducer is as follows: 1) 4.14g of 2-acrylamido-2-methylpropanesulfonic acid, 7.2g of acrylic acid, 4.12g of sodium p-styrenesulfonate, 2.13g of acrylamide and 17.6g of water are stirred and dissolved uniformly to prepare a mixed aqueous solution with a mass concentration of 50%, and 0.4wt.% of sodium hydroxide aqueous solution is added dropwise to adjust the pH of the reaction system to 5, and after stirring and heating to 55°C, 0.70g of ammonium persulfate and 0.37g of thioglycolic acid are added, and the reaction is continued at 55°C for 4h to obtain a polyacrylic acid macromonomer; 2) Add 215 g of vinyl acetate, 0.15 g of isopropanol and 758 g of water to the polyacrylic acid macromonomer, stir for 10 min between each addition, then heat to 75° C., and then drop 13.95 g of a 20 wt.% aqueous solution of dibenzoyl peroxide thereto for 2 h. After the addition is completed, continue to stir and react at a constant temperature for 2 h. After the reaction is completed, adjust the pH of the system to 6 with a 0.4 wt.% aqueous solution of sodium hydroxide, cool naturally, and obtain a drag reducer with a concentration of 30%.

[0040] Example 4

[0041] A non-dispersible cement slurry system for cementing water comprises, by weight, 100 parts of G-grade oil well cement, 2 parts of swelling agent, 3 parts of anti-dispersant, 1.2 parts of drag reducer, 0.1 parts of defoamer and 42 parts of water, and is prepared according to the method specified in the standard GB / T 19139 oil well cement test method; wherein, in this embodiment 4, the specific selection of G-grade oil well cement, swelling agent, defoamer, anti-dispersant and defoamer is consistent with that in embodiment 1.

[0042] Comparative Example 1

[0043] A cement slurry system for cementing water that does not disperse, characterized by comprising, by weight, 100 parts of G-grade oil well cement, 2 parts of expansion agent, 0.5 parts of drag reducer, 0.1 parts of defoamer and 43 parts of water. The only difference between this comparative example 1 and example 2 is that no anti-dispersant is added in comparative example 1.

[0044] Comparative Example 2

[0045] A cement slurry system for cementing water that does not disperse, characterized by comprising, by weight, 100 parts of G-grade oil well cement, 2 parts of expansion agent, 2 parts of anti-dispersion agent, 0.1 parts of defoaming agent and 43 parts of water. The only difference between this comparative example 2 and example 2 is that no drag reducer is added in comparative example 2.

[0046] Comparative Example 3

[0047] A cement slurry system for cementing water that does not disperse, characterized by comprising, by weight, 100 parts of G-grade oil well cement, 2 parts of expansion agent, 2 parts of anti-dispersion agent, 0.5 parts of commercially available drag reducer, 0.1 parts of defoamer and 43 parts of water. The only difference between this comparative example 3 and example 2 is that the drag reducer in comparative example 3 uses a commercially available polycarboxylic acid drag reducer D.

[0048] Performance Test:

[0049] (I) Evaluation of anti-dispersion of cement slurry system with non-dispersible water for cementing:

[0050] In the anti-dispersion evaluation experiment, the anti-dispersion of the water-cement slurry systems prepared in Examples 1-4 and Comparative Examples 1-3 was evaluated using cement loss determination method, pH value method and water-land strength ratio in turn.

[0051] Experimental determination method of cement loss: First, take a 1000mL beaker and fill it with 800mL of distilled water; then, pour 680g of cement slurry stirred in a normal pressure viscosifier at 80℃ for 20min into the beaker, and require the slurry to slowly and freely fall from the water surface of the beaker into the container within 2min. After standing for 5min, pour out 600mL of the upper solution, stir evenly, and use a digital liquid densitometer to determine its density; multiply the obtained density by 600mL and subtract 600g of the weight of the water itself to obtain the weight of the solid phase particles dispersed in the 600mL water in the upper layer of the beaker due to the flushing effect of water when 680g of cement slurry is poured into the container.

[0052] Experimental method for pH determination: First, take a 1000mL beaker and fill it with 800mL of distilled water; then, pour 680g of cement slurry stirred in a normal pressure viscometer at 80℃ for 20min into the beaker, and require the slurry to fall slowly and freely from the water surface of the beaker mouth into the container within 2min, let it stand for 5min, and within 30s, use a pipette to draw 10mL of solution from the upper solution of the beaker as the experimental sample, and use precision pH test paper to determine its pH value. Since the pH value of cement slurry itself is high, and the pH value of water is neutral, if water intrusion occurs when cement slurry falls freely from water, and cement particles are dispersed and segregated, the pH value of water will increase significantly.

[0053] The test method of water-land strength ratio is as follows: put the strength mold into water at a height of 40 cm, then pour the cement slurry into it from above the water surface, take it out after the mold is filled with cement slurry, and cure it for 24 hours under the specified experimental conditions (80°C, normal pressure), and measure the compressive strength of the cement paste; calculate the ratio of the compressive strength value of the cement paste to the strength value of the cement paste on land as the water-land strength ratio, which is used to evaluate the anti-dispersion property of the cement paste; among them, the larger the ratio of the water-land strength ratio, the better the anti-dispersion property of the cement paste.

[0054] The specific test results of the above three experiments are shown in Table 1 below.

[0055] Table 1:

[0056] Cement slurry system Cement loss (g) pH Ratio of water to land strength Example 1 7 9 0.67 Example 2 5 8 0.79 Example 3 3 8 0.81 Example 4 3 8 0.84 Comparative Example 1 30 13 - Comparative Example 3 19 11 0.68

[0057] It can be seen from the test results in Table 1 that the cement slurry systems prepared in Examples 1 to 4 of the present application all have good anti-dispersion performance, and compared with Comparative Example 1, the addition of anti-dispersion agent has a significant effect on improving the anti-dispersion ability of cement slurry; compared with Comparative Example 3, the drag reducer of the present application is better when used in combination with the anti-dispersion agent compared with the commercially available drag reducer, and the cement loss amount is greatly reduced.

[0058] In addition, since no drag reducer was added in Comparative Example 2, the cement slurry system was too thick and the above three tests could not be performed; and the anti-dispersants currently available on the market are all anti-dispersants used in the construction industry, which are completely unsuitable for the oil well cement slurry system of the present application.

[0059] (II) Evaluation of rheological properties of non-dispersible cement slurry system for cementing water:

[0060] The rheological properties of the cement slurry systems of Example 2, Comparative Example 2 and Comparative Example 3 were tested according to the method specified in the standard GB / T19139-2012 “Test methods for oil well cement”.

[0061] The test results are shown in Table 2 below.

[0062] Table 2:

[0063]

[0064] It can be seen from the test results in Table 2 that the cement slurry system of Comparative Example 2 is only added with an anti-dispersant, but no drag reducer, resulting in poor flowability of the cement slurry, which cannot meet the requirements of on-site pumping. Compared with Example 2, the present application adds an anti-dispersant and a drag reducer to the oil well cement, so that the cement slurry has excellent anti-dispersibility while having good rheological properties, meeting the requirements of on-site construction. It also shows that the anti-dispersant and the drag reducer of the present application have good compatibility. Compared with Comparative Example 3, Example 2 shows that the drag reducer disclosed in the present application has a better coordination effect with the anti-dispersant disclosed in the present application, compared with the commercially available drag reducer, the consistency coefficient is significantly reduced, and the rheological properties are more excellent.

Claims

1. A cement slurry system for cementing water that does not disperse, characterized in that: The invention comprises 100 parts of oil well cement, 2 to 3 parts of expansion agent, 1 to 5 parts of anti-dispersant, 0.5 to 2 parts of drag reducer, 0 to 0.1 parts of defoamer and 40 to 45 parts of water in parts by weight; wherein the anti-dispersant is composed of 15 wt.% to 60 wt.% of acrylic acid, 0 wt.% to 15 wt.% of N,N-dimethylacrylamide, 30 wt.% to 85 wt.% of acrylamide, 0 wt.% to 10 wt.% of N-vinylpyrrolidone, 0 wt.% to 1.5 wt.% of disodium ethylenediaminetetraacetate in parts by weight. A polyacrylamide flocculant obtained by copolymerization; the drag reducer is obtained by graft polymerization of fatty acid vinyl ester and polyacrylic acid monomer; the polyacrylic acid monomer is obtained by copolymerization of 2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium p-styrenesulfonate and acrylamide in a molar ratio of (0.08-0.6):1:(0.05-0.3):(0.1-1.0); the molar ratio of acrylic acid in the preparation of fatty acid vinyl ester and polyacrylic acid monomer is (8-36):1; the fatty acid vinyl ester is at least one of vinyl acetate, vinyl propionate and vinyl butyrate.

2. The non-dispersible cement slurry system for cementing water according to claim 1, characterized in that: The oil well cement is API oil well G grade cement.

3. The non-dispersible cement slurry system for cementing water according to claim 1, characterized in that: The specific preparation method of the anti-dispersant is: Step 1, preparing 5wt.% to 30wt.% acrylic acid aqueous solution, and adding a pH adjuster dropwise to make the pH of the reaction system 4 to 9; Step 2, adding N,N-dimethylacrylamide, acrylamide, N-vinyl pyrrolidone and disodium ethylenediaminetetraacetate to the reaction system, and stirring until dissolved; Step 3, introducing an inert gas into the reaction system for at least 20 minutes, and then placing the reaction system at 30°C to 40°C, sequentially adding initiator A and initiator B into the reaction system, and stirring until dissolved; Step 4: Place the reaction system under sealed conditions and continue the reaction at 30° C. to 40° C. for 2 h to 4 h to obtain a translucent gel-like anti-dispersion flocculant.

4. The non-dispersible cement slurry system for cementing water according to claim 3, characterized in that: In the preparation step 3 of the anti-dispersant, initiator A is azomethylpropylimidazole hydrochloride, and its addition amount is 0.1wt.% to 1wt.% of the total weight of the comonomer; initiator B is a mixture of potassium persulfate and sodium bisulfite, and its addition amount is 0.1wt.% to 1wt.% of the total weight of the comonomer.

5. The non-dispersible cement slurry system for cementing water according to claim 1, characterized in that: The specific preparation method of the drag reducer is: Step 1, dissolving 2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium p-styrenesulfonate and acrylamide in water to prepare a 40wt.% to 60wt.% reaction solution, and dropping a pH adjuster to adjust the pH of the reaction system to 2.5 to 6.5, then stirring and heating to 40°C to 80°C, adding initiator A and a chain transfer agent to the reaction system, and continuing the isothermal reaction under the above temperature conditions for 3h to 6h to obtain a polyacrylic acid macromonomer; Step 2: Add fatty acid vinyl ester, molecular weight regulator and water to the polyacrylic acid macromonomer in sequence, stir and dissolve, heat the reaction system to 50°C to 90°C, and drop 20wt.% to 40wt.% of an aqueous solution of initiator B, and then continue to stir and react at a constant temperature for 1h to 3h; after the reaction is completed, drop a pH regulator to adjust the pH of the system to 5 to 7, and after cooling, obtain a graft copolymer drag reducer with a concentration of 20% to 40%.

6. The non-dispersible cement slurry system for cementing water according to claim 1, characterized in that: In the preparation step 1 of the drag reducer, the initiator A is ammonium persulfate, potassium persulfate or sodium persulfate, and its amount is 0.8wt.% to 5.0wt.% of the total weight of 2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium p-styrenesulfonate and acrylamide; the chain transfer agent is mercaptopropionic acid, thioglycolic acid or sodium methacrylic acid, and its addition amount is 0.01 to 0.05 times the molar amount of acrylic acid.

7. The non-dispersible cement slurry system for cementing water according to claim 1, characterized in that: In the preparation step 1 of the drag reducer, the molecular weight regulator is n-dodecyl mercaptan or isopropanol, and the amount thereof added is 0.0005 to 0.001 times the molar amount of the fatty acid vinyl ester; the initiator B is dibenzoyl peroxide, lauroyl peroxide, diisopropyl peroxydicarbonate or dicyclohexyl peroxydicarbonate, and the amount thereof added is 0.8% to 1.5% of the total weight of 2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium p-styrenesulfonate, acrylamide and fatty acid vinyl ester.

8. The non-dispersible cement slurry system for cementing water according to claim 3 or 5, characterized in that: The pH adjuster is a 0.4 wt. % sodium hydroxide aqueous solution or a 0.4 wt. % potassium hydroxide aqueous solution.

9. The non-dispersible cement slurry system for cementing water according to claim 1, characterized in that: The defoaming agent is a silicone ether copolymer defoaming agent, a polyether defoaming agent or a lipid defoaming agent.

Citation Information

Cited By

  • Underwater non-dispersible cement slurry system for ocean well cementation based on charge self-attraction and preparation method thereof

    CN121651773A

  • Coal gangue-based concrete high-performance rheology modifier as well as preparation method and application thereof

    CN122233676A